2017
DOI: 10.2337/cd16-0011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Back Pain: Markers of Diabetes Disease Progression Are Associated With Chronic Back Pain

Abstract: IN BRIEF Diabetes has been associated with the incidence of back pain. However, the relationship between markers of diabetes progression and back pain has not been studied. The objective of this study was to correlate clinical and laboratory measures of diabetes disease severity to the presence of back pain to provide insight into the relationship between these conditions. Findings showed that markers of diabetes disease progression were associated with the presence of back pain, suggesting that uncontrolled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…However, chronic diseases in this study were assessed by asking employees about their current diabetes and hypertension condition, not by asking the duration of the diseases. A study showed that diabetes progression is positively associated with the presence of back pain [37]. However, we found a similar result of no association between physical activity and low back pain [38].…”
Section: Discussionsupporting
confidence: 59%
“…However, chronic diseases in this study were assessed by asking employees about their current diabetes and hypertension condition, not by asking the duration of the diseases. A study showed that diabetes progression is positively associated with the presence of back pain [37]. However, we found a similar result of no association between physical activity and low back pain [38].…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, compelling evidence suggests that people who suffer from type 2 diabetes and back pain usually present with greater signs of poor general health (e.g. hypertension and dyslipidemia) and progress to worse outcomes such as increased pain severity [6, 34, 36, 37]. In agreement with previous studies, we found that type 2 diabetes was more strongly associated with severe cases of chronic spinal pain (adjusted OR 3.33, 95% CI 1.47 to 7.53), NP (adjusted OR 2.28, 95% CI 1.24 to 4.21), and LBP (adjusted OR 1.63, 95% CI 1.00 to 2.64).…”
Section: Discussionmentioning
confidence: 99%
“… 5 In a patient material, markers of diabetes progression were associated with the presence of back pain. 28 A Finnish cross-sectional study showed an association between chronic widespread pain including back pain and both diabetes and prediabetes. 29 …”
Section: Discussionmentioning
confidence: 99%